The Validity of Cross Priming Amplification to Detect SARS-CoV-2 Virus - Luhung Budiailmiawan; Ryan Bayusantika Ristandi; Azzania Fibriani (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
The standard molecular technique to detect the SARS-CoV-2 virus is The Real-Time Reverse-Transcription Polymerase Chain Reaction (rRT-PCR). It requires sophisticated equipment and a time-consuming sample process. The Cross Priming Amplification (CPA) is a nucleic acid amplification technique that amplifies DNA with high specificity and efficiency under constant thermal conditions. This technique is faster than rRT-PCR and doesn't require a biosafety level-2 (BSL-2) facility. The study aimed to determine the validity of CPA with rRT-PCR as a gold standard and to evaluate its performance as molecular rapid tests for detecting SARS-CoV-2 RNA from nasopharyngeal swab specimens. This study was a descriptive diagnostic test by using data retrospectively from swab nasopharyngeal patient samples who were treated at Palabuhan Ratu Hospital with COVID-19 from 01 January to 31 December 2021. The CPA was performed on a total of 52 nasopharyngeal samples at Pelabuhan Ratu Laboratory and rRT-PCR at Provincial Health Laboratory. The validity and correlation tests were performed. The majority of subjects were female between the ages of 34-50 years. The cut-off Tt-value is 3.25, 0.84 Area Under Curve (AUC), with a p-value <0.001. The CPA has good validity for COVID-19 diagnosis with 77% sensitivity, 94% specificity, 96% PPV, and 71% NPV. The sensitivity was increasing with Ct-value <30 (82%) and Ct-value <25 (87%). The CPA had a good validity for the COVID-19 diagnostic test. The CPA could be used as a rapid molecular test for detecting SARS-CoV-2 viral RNA from nasopharyngeal swab specimens.